Repetitive transcranial magnetic stimulation in treatment-seeking subjects with cocaine use disorder: A randomized, double-blind, sham-controlled trial - Martinotti, Giovanni; Pettorruso, Mauro; Montemitro, Chiara; Spagnolo, Primavera Alessandra; Acuti Martellucci, Cecilia; Di Carlo, Francesco; Fanella, Fabrizio; di Giannantonio, Massimo (Progress in neuro-psychopharmacology & biological psychiatry, 2022)
Cocaine use disorder (CUD) is a chronic and relapsing brain disorder with no approved treatments. Repetitive transcranial magnetic stimulation (rTMS) has shown promising results in open label and single-blind studies, reducing cocaine craving and consumption. Although, large randomized, double-blind, controlled trials are still missing. This multi-center, randomized, double-blind, sham-controlled study was designed to evaluate the safety and efficacy of multiple sessions of active rTMS compared to sham stimulation in patients with CUD. rTMS (15 Hz, 2 daily sessions for 5 days/week,for a total of 20 stimulation sessions) was delivered over the left DLPFC for two weeks of continuous treatment followed by 12 weeks of maintenance (1 day/week, twice a day), in a double-blind, randomized sham-controlled design. Our primary outcomes included self-reported cue-induced craving and cocaine consumption, as measured by percentage of negative urine tests. Our secondary outcomes included: 1) changes in depressive symptoms; 2) changes in cocaine withdrawal symptoms; and 3) changes in self-reported days of cocaine use. Forty-two outpatients with CUD were enrolled in the active rTMS group and 38 patients in the sham group. We observed a significant decrease in self-reported cue-induced cocaine craving and consumption in both the active rTMS and sham, whereas no main effect of treatment was found. However, the active rTMS group showed greater changes in depressive symptoms. The improvement on depressive symptomatology was particularly marked among patients receiving a total number of rTMS sessions greater than 40 and those reporting more severe depressive symptoms at baseline. A significant improvement of CUD symptoms during active rTMS treatment was observed. However, we did not observe significant differences in cocaine craving and consumption between treatment groups, highlighting the complexity of factors contributing to CUD maintenance. A significant improvement in depressive symptoms was observed in favour of the active group. Clinical trial registration details:clinicaltrials.govidentifierNCT03333460 •Efficacy of transcranial magnetic stimulation in cocaine use disorder was evaluated.•Main outcomes were cocaine craving and percentage of negative urine tests for cocaine.•Both active and sham groups showed improvement in the main outcomes.•There was no significant difference between active and sham groups as to main outcomes.•A significant improvement of depressive symptoms appeared in favour of the active group.